From Civilizational Aspiration to Foreign Policy Deliverability: Indonesia’s “Game Changer” Narrative - Jacob Junian Endiartia (Indonesian Perspective, 2026)
This article reframes the “game changer” thesis in Indonesian foreign policy as a programmatic form of strategic imagination rather than a predictive claim about national ascent. Drawing on Anis Matta’s Gelombang Ketiga Indonesia (2014) and Indonesia sebagai Game Changer (2024), the study reconstructs a repertoire of role claims—model-maker, bridge-builder, agenda-setter, humanitarian leader, and system-builder—and translates them into implied policy demands. These demands are filtered through a structured policy capacity diagnostic (analytical–operational–political × individual–organizational–systemic). Using focused Indonesia-centered illustrations, the article shows that deliverability hinges less on narrative ambition than on recurrent capacity signatures, particularly organizational–operational coordination and systemic–political legitimation. Adaptations such as quiet diplomacy, selective enactment, and narrative governance emerge as capacity-congruent outcomes rather than simple failure. The study contributes by linking role theory and policy capacity into a portable deliverability framework applicable to Muslim-majority democracies facing high civilizational ambition under institutional constraint.